Breeding of winter rapeseed inbred lines for the development of parent forms for hybrids - E. B. Bochkaryova; L. A. Gorlova; V. V. Serdyuk; E. A. Strelnikov (Труды по прикладной ботанике, генетике и селекции)
Introduction. The V.S. Pustovoit All-Russian Research Institute of Oil Crops (VNIIMK) performs the breeding of interline rapeseed hybrids using the Ogura CMS. The program of interline winter rapeseed hybrid development was aimed at studying the efficiency of self-pollinated line breeding from population cultivars, assessing the impact of inbreeding depression on economically important traits, analyzing the changes in the lines’ traits after their transition to the sterile basis, and obtaining fertility restorer lines with an acceptable level of glucosinolate content in seeds.Materials and methods. Intraspecific hybrids, cultivars developed at the Pustovoit Institute and those of foreign breeding were employed as parent material for the development of self-pollinated lines. Self-pollination of rapeseed plants was performed using spunbond isolators. Over 1000 plants were self-pollinated every year. Generations of self-pollinated lines S1 –S4 were planted on 2.25 m2 plots, and during the growth season their visual screening was undertaken to assess their morphobiological traits. Starting with S5, the lines were evaluated for their yield on 7.5 m2 plots.Results. The inbreeding depression was found to not exceed 3–15% of the seed yield. The transition of the lines to sterile cytoplasm did not have any negative consequences. A series of experimental hybrids were developed, exceeding the reference cultivar ‘Loris’ in seed yield by 23–48%. New hybrid combinations also exceeded the reference in seed yield by 21–54%.